Power system reliability considering combined cycle plants - Alemany, Juan Manuel (2010)
In the nineties in Argentina, the growth of thermal power generation was mainly based on combined cycle plants. Currently, one problem associated with the use of combined cycle plants is the fact that they need to share the use of natural gas with commercial, industrial and domestic uses. Hence, the natural gas availability is becoming a critical issue. Therefore, power system reliability studies must consider fuel availability into the models, and as a consequence, reliability models must take into account the joint operation of electrical generation and natural gas systems. The aim of this paper is to evaluate the influence of combined cycle plants on reliability studies applied to system generation capacity and their dependency on natural gas availability. Monte Carlo simulation method is used to determine reliability indices such as Loss of Load Expectation, Loss of Energy Expectation, Loss of Load Frequency, and Loss of Load Duration. The IEEE RTS 96 test system is used as the base system, with is modified in order to incorporate combined cycle plants.